Validation and Analysis of an Achievement Test in the Subject of Biology at the Secondary Leve - Anjum Asmat, Farah Latif Naz (JSE, 2023)
A reliable and valid test is essential to measure students learning outcomes. The present study was designed to construct a valid Biology test and to analyze the achievement of 9th -grade science students. The sample of the present study was two hundred and nine (209) students who were selected from nine Government schools and private schools by using a simple random sampling technique.